(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
تناولت الدراسة مقارنة ثلاثة كواشف (أستيل أسيتون, أسيتو أسيت أنيليد, ملح ثنائي الصوديم لحمض الكروموتروبيك) المستخدمة في تحديد الفورم ألدهيد بغية تثبيت الشروط التحليلية المثلى لكل كاشف من هذه الكواشف وفق تقانة الطيف المرئي (VIS-Spectrophotometer)، ومن ثمَّ المقارنة في ما بينها بغية تحديد الكاشف الأمثل والشروط المثلى التي يمكن من خلالها الوصول في تحديد الفورم ألدهيد إلى أدنى حد كشف ممكن، ومقارنة النتائج المترتبة عن هذه الدراسة مع دراسات أخرى استخدمت الكواشف نفسها، إنما بشروط تحليلية مغايرة. تمَّ تخفيض حد كشف كاشف ملح ثنائي الصوديوم لحمض الكروموتروبيك إلى ما بين (0.0100 – 0.0125ppm) مع نسبة استرجاع تراوحت بين (108.543 - 119.444%), وذلك اعتماداً على تكرارية ثلاث تجارب (عينات مستقلة) منفصلة متتالية، وهو حد كشف أخفض بمقدار النصف عن حد الكشف 0.02ppm المُسجل وفق طريقة (NIOSH 3500). This study deals with the comparison of (Acetyl acetone, Acetoacetanilide, chromotropic acid disodium salt) used as reagents for determine formaldehyde, and to fixed the optimal analytical conditions of the above signed reagents using VIS-Spectrophotometer. The optimal analytical conditions of each reagent are compared with each other in order to determine the optimal reagent and conditions which allow to determining formaldehyde as possible at its lowest detection limit. The results of this study are compared with other studies used the same reagents, but by contrast analytical conditions. The lowest detection limit for chromotropic acid disodium salt ranged between (0.0100 – 0.0125ppm) with recovery ranged between (108.543- 119.444%) depending on the reproducibility of three sequence separated experiments (independent samples). This detection limit is twice times lower than the detection limit 0.02ppm registered according to the study achieved by method (NIOSH 3500).